Real-World Effectiveness and Safety of Intravenous Daratumumab in Patients with Multiple Myeloma: A Multicenter, Observational Study from Korea - Koh, Youngil; Yoon, Sung-Soo; Kim, Kihyun; Lee, Je-Jung; Jung, Sung-Hoon; Yoon, Sang Eun; Park, Sung-Soo; Park, YoungJu; Yoon, Soomin; Min, Chang-Ki (Cancer research and treatment, 2025)
Purpose Daratumumab is a novel, first-in-class monoclonal antibody approved for use as monotherapy and in combination with other treatments for patients with multiple myeloma (MM). The aim of this observational study was to evaluate the effectiveness and safety of daratumumab in real-world clinical practice.Materials and Methods This observational multicenter study collected data from patients with MM treated in Korea between June 1, 2018, and February 28, 2022.Results A total of 125 patients with a diagnosis of MM were included and followed until discontinuation or completion of 52 weeks’ follow-up. The median age was 67 years, and 97.6% of patients received more than three prior lines of therapy. The overall response rate was 52.5% (95% confidence interval [CI], 43.2 to 61.8), and a very good partial response was observed in 19.5% of patients (95% CI, 12.8 to 27.8). Of the patients who achieved a partial or higher response (52.5%), the median time to first response was 2.4 months (95% CI, 1.8 to 3.4), and the median time from start of daratumumab treatment until progressive disease was 4.1 months (95% CI, 2.9 to 5.1). Fever (24.0%) was the most frequently recorded adverse event (AE), while anemia (8.8%) and neutropenia (8.0%) were the most frequently observed grade 3-4 AEs. Overall, no unexpected safety signals were observed.Conclusion In a rapidly evolving treatment landscape, this analysis provides insight into the real-world outcomes for patients with MM receiving daratumumab in Korea and reveals that real-world outcomes were improved over results demonstrated in a clinical trial setting.